2016
DOI: 10.2147/ott.s109736
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of pretreatment albumin/globulin ratio in patients with hepatocellular carcinoma

Abstract: BackgroundPretreatment nutritional and immunological statuses play an indispensable role in predicting the outcome of patients with various types of malignancies. The purpose of this study is to evaluate the predictive value of albumin/globulin ratio (AGR) in overall survival (OS) and recurrence in patients with hepatocellular carcinoma (HCC) following radical hepatic carcinectomy.Patients and methodsThis retrospective study included a total of 172 patients with HCC with complete medical and follow-up informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 54 publications
1
46
0
Order By: Relevance
“…The albumin/ globulin ratio (AGR) can be calculated by measuring the total serum protein and albumin concentrations. The AGR can be used for prognostic evaluation of tumors (4,5). Although serum albumin and globulin were thought to correlate with AECOPD progression, few reports have described the application of the AGR to AECOPD (3,6).…”
Section: Original Articlementioning
confidence: 99%
“…The albumin/ globulin ratio (AGR) can be calculated by measuring the total serum protein and albumin concentrations. The AGR can be used for prognostic evaluation of tumors (4,5). Although serum albumin and globulin were thought to correlate with AECOPD progression, few reports have described the application of the AGR to AECOPD (3,6).…”
Section: Original Articlementioning
confidence: 99%
“…Numerous factors have been identified as prognostic indicators and are incorporated into various staging systems. These factors include lesion numbers, vascular invasion, portal hypertension, regional lymph node metastases, distant metastases, laboratory examination indicators such as serum albumin and bilirubin, and so on. Tumor size has been included in several staging systems, such as the Liver Cancer Study Group of Japan TNM staging system and the Hong Kong staging system .…”
Section: Introductionmentioning
confidence: 99%
“…The association of AGR and mortality had been reported by previous studies on varied populations, including non-ST elevation myocardial infarction [19], colorectal cancer [20,21], hepatocellular carcinoma [22], and early-stage non-small cell lung cancer [23]. Suh et al reported low AGR was a risk factor for cancer incidence and mortality, both in the short-and long terms, in 26,974 healthy patients [24].…”
Section: Discussionmentioning
confidence: 76%